2007
DOI: 10.1021/ja076134v
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Plasmon-Induced Electron Transfer from Gold Nanodots into TiO2 Nanoparticles

Abstract: By using femtosecond transient absorption spectroscopy with visible pump and IR probe to observe generation of injected electrons, we could directly observe plasmon-induced electron transfer from 10 nm gold nanodots to TiO2 nanocrystalline film. It was revealed that the reaction time was within 240 fs and the yield was about 40%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
896
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 919 publications
(945 citation statements)
references
References 18 publications
42
896
5
2
Order By: Relevance
“…13d A similar route was also proposed for an organic solar cell system composed of ZnPc/Ag/ITO, in which it was assumed that "free" electron gas transfers energy to one electron, which in its exited state can fill the empty state of ITO (in our case CB of titania), if it has momentum perpendicular to the contact area, and at the same positive charge, the empty state left in the metal particle has to be filled again with 5 an electron from ZnPc (in our case from OCs); 47 Furube et al reported direct observation of electron transfer from gold nanodots to titania particles using femtosecond transient absorption spectroscopy with an IR probe. 48 However, estimated reaction time (240 fs) seemed to be much longer than the lifetime of the gold LSPR excitation state, presumably caused by limited time resolution of their instrumental setups. Using a setup with time 10 resolution < 50 fs, direct electron transfer from gold to titania was suggested.…”
Section: (2)mentioning
confidence: 99%
“…13d A similar route was also proposed for an organic solar cell system composed of ZnPc/Ag/ITO, in which it was assumed that "free" electron gas transfers energy to one electron, which in its exited state can fill the empty state of ITO (in our case CB of titania), if it has momentum perpendicular to the contact area, and at the same positive charge, the empty state left in the metal particle has to be filled again with 5 an electron from ZnPc (in our case from OCs); 47 Furube et al reported direct observation of electron transfer from gold nanodots to titania particles using femtosecond transient absorption spectroscopy with an IR probe. 48 However, estimated reaction time (240 fs) seemed to be much longer than the lifetime of the gold LSPR excitation state, presumably caused by limited time resolution of their instrumental setups. Using a setup with time 10 resolution < 50 fs, direct electron transfer from gold to titania was suggested.…”
Section: (2)mentioning
confidence: 99%
“…As illustrated in the energy diagram in Figure 6, it is hypothesized that an excited electron is transferred to the conduction band of TiO 2 immediately following the inter-or intraband transition of the Au nanoparticles induced by the plasmonically enhanced optical near-field, 58 thus leaving a hole trapped to the surface states of the TiO 2 near the Au/TiO 2 /water interface; the trapped holes can subsequently induce the oxidation of water molecules. 59 It is possible for multiple holes to form and become trapped at the restricted nanospace near the Au/TiO 2 interface because the plasmonically enhanced optical near-field is induced at both ends of the Au nanoparticles, especially at the Au/TiO 2 /water interface, as determined using electromagnetic simulations.…”
Section: Mechanism Of Photoelectric Conversionmentioning
confidence: 99%
“…3), the Au/g-C 3 N 4 composite (red curve) shows an additional absorption peak around 550 nm, which can be attributed to the surface plasmon of Au nanoparticles. 40 However, for the CdS/Au/g-C 3 N 4 composite, the absorption around 550 nm disappears (blue curve in the inset of Fig. 3) due to the formation of CdS shell on Au.…”
mentioning
confidence: 96%